Chemoselective and stereoselective lithium carbenoid mediated cyclopropanation of acyclic allylic alcohols. Issue 9 (5th February 2016) - Durán-Peña, M. J.; Flores-Giubi, M. E.; Botubol-Ares, J. M.; Harwood, L. M.; Collado, I. G.; Macías-Sánchez, A. J.; Hernández-Galán, R.
Abstract : A new method for the chemo- and stereoselective conversion of acyclic allylic alcohols into the corresponding substituted cyclopropane derivatives has been developed using lithium carbenoids. Abstract : The reaction of geraniol with different lithium carbenoids generated from n -BuLi and the corresponding dihaloalkane has been evaluated. The reaction occurs in a chemo and stereoselective manner, which is consistent with a directing effect from the oxygen of the allylic moiety. Furthermore, a set of polyenes containing allylic hydroxyl or ether groups were chemoselectively and stereoselectively converted into the corresponding gem -dimethylcyclopropanes in one single step in moderate to good yields mediated by a lithium carbenoid generated in situ by the reaction of n -BuLi and 2, 2-dibromopropane.